(untitled) (International Journal of Scientific Research in Science and Technology, 2024)
The proposed anti-theft vehicle security system introduces a robust authentication framework to bolster security measures. Through the fusion of fingerprint recognition, facial scanning, and One-Time Password (OTP) verification, the system establishes multiple layers of user authentication. This multi-step process ensures that only authorized individuals can gain access to the vehicle’s ignition system. Furthermore, the system integrates advanced features such as real-time location tracking using GPS technology and remote alerts via GSM communication. These functionalities empower vehicle owners with the ability to monitor their vehicle’s whereabouts and receive immediate notifications in the event of unauthorized access or suspicious activities. In addition to its authentication capabilities, the system incorporates surveillance elements to enhance security further. A USB web camera is employed to capture images of the vehicle’s surroundings, facilitating potential identification of unauthorized users. The user interface, comprising an LCD display, LEDs, and a buzzer, provides intuitive feedback on authentication status and alerts users to potential security threats. By combining advanced authentication methods with robust surveillance and user feedback mechanisms, the system aims to effectively deter theft and unauthorized access while offering vehicle owners peace of mind and control over their vehicle’s security.